2014
DOI: 10.1177/0886260514564157
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Abuse Against Women Who Have Attempted Suicide by Deliberate Self-Poisoning

Abstract: Sources of data about the occurrence of domestic violence are scarce in Iran. The aim of this study was to evaluate the behavioral effects of different types of domestic violence on women who had attempted suicide by deliberate self-poisoning (DSP). A total of 195 women who had attempted suicide by DSP in response to "violence and abuse" were followed up for 2 years. The most common type of violence, as mentioned by the women themselves as the motive of self-poisoning, was physical abuse (92%) followed by verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(22 reference statements)
3
6
0
Order By: Relevance
“…Our patients were predominantly female which may be due to the more prevalent depression and suicidal gesture actions in women in the Middle East region. [ 23 ] It also seems that using the tablet ingestion method for suicide in women is more common which is consistent with previous studies. [ 13 ] The average age of the patients was 25.4 years and the most prevalent age class was 20-29 years, which could be due to more prevalent prescription of carbamazepine for the youth as an anticonvulsant drug, here in Iran.…”
Section: Discussionsupporting
confidence: 89%
“…Our patients were predominantly female which may be due to the more prevalent depression and suicidal gesture actions in women in the Middle East region. [ 23 ] It also seems that using the tablet ingestion method for suicide in women is more common which is consistent with previous studies. [ 13 ] The average age of the patients was 25.4 years and the most prevalent age class was 20-29 years, which could be due to more prevalent prescription of carbamazepine for the youth as an anticonvulsant drug, here in Iran.…”
Section: Discussionsupporting
confidence: 89%
“…Further, the majority of MCs believed that the male victims’ rights are disregarded in Iran just because DV against men is less common than that against women. Finally, the main causes of DV, as reported by the commentators were found to include poverty, education, and the economic status of the country, echoing the findings of Hassanian-Moghaddam et al (2014) and Amanat et al (2019).…”
Section: Discussionmentioning
confidence: 69%
“…The concept of MDFs illustrates that men have a more dominant role in the family. Studies on domestic violence in various countries have revealed that experiencing domestic violence has been a decisive factor for women in committing suicide (Hassanian-Moghaddam et al, 2016; Kuhlman et al, 2016). Domestic violence where women are the victims shows that women are often subject to various forms of violence by their husbands.…”
Section: Resultsmentioning
confidence: 99%